2022
DOI: 10.1039/d1sc06102j
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki-type cross-coupling of alkyl trifluoroborates with acid fluoride enabled by NHC/photoredox dual catalysis

Abstract: The Suzuki–Miyaura cross-coupling of C(sp3)-hybridised boronic compounds still remains a challenging task, thereby hindering the broad application of alkyl boron substrates in carbon-carbon bond-forming reactions. Herein, we developed an NHC/photoredox...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“…In this catalytic cycle, sensitization of an NHC catalyst induced a SET process with an acyl fluoride, leading to subsequent radical−radical recombination between ketyl and benzyl radicals. 115 Although the highest yield was observed with [Ir(dtbbpy)(ppy) 2 ]PF 6 , 4CzIPN still produced a moderate yield of 25%. DFT calculations also showed that the azolium intermediates had a lower triplet energy level than the PCs, confirming that triplet sensitization is possible.…”
Section: ■ E → Z Isomerization Of Olefinsmentioning
confidence: 93%
See 1 more Smart Citation
“…In this catalytic cycle, sensitization of an NHC catalyst induced a SET process with an acyl fluoride, leading to subsequent radical−radical recombination between ketyl and benzyl radicals. 115 Although the highest yield was observed with [Ir(dtbbpy)(ppy) 2 ]PF 6 , 4CzIPN still produced a moderate yield of 25%. DFT calculations also showed that the azolium intermediates had a lower triplet energy level than the PCs, confirming that triplet sensitization is possible.…”
Section: ■ E → Z Isomerization Of Olefinsmentioning
confidence: 93%
“…Finally, the Li group reported a photocatalyzed Suzuki-type coupling involving potassium trifluoroborates and N -heterocyclic carbenes (NHCs) (Scheme ). In this catalytic cycle, sensitization of an NHC catalyst induced a SET process with an acyl fluoride, leading to subsequent radical–radical recombination between ketyl and benzyl radicals . Although the highest yield was observed with [Ir­(dtbbpy)­(ppy) 2 ]­PF 6 , 4CzIPN still produced a moderate yield of 25%.…”
Section: Cross-couplingmentioning
confidence: 99%
“…The photoredox catalysis cycle is closed by the SET reduction of the acyl azolium intermediate, providing the corresponding ketyl radical. Using the same strategy with alkyl trifluoroborates and acid fluorides as substrates, Li established an NHC/photoredox dual-catalysis system which enables rapid access to various ketones . Recently, Ohmiya and co-workers demonstrated a visible-light-driven silyl radical generation with silylboronates as the substrates .…”
Section: Ketyl Radicals Generated Via Single-electron Reduction Using...mentioning
confidence: 99%
“…Recently, Li developed a NHC/photoredox dual catalytic cross-coupling of alkyl trifluoroborates with acid fluorides, providing an alternative solution to the classical acylative Suzuki coupling chemistry (Scheme 32). 44 Scheme 32 NHC/photoredox catalyzed Suzuki-type cross-coupling between alkyl trifluoroborates and acid fluorides 44…”
Section: Organoborane Reagentsmentioning
confidence: 99%